PERSONALITY-ORIENTED APPROACH DURING THE TRAINING OF FOREIGN LANGUAGE TEACHERS: PROBLEMS AND PROSPECTS (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the question of the personality - oriented approach to teachers' training. The proposed methodology has been theoretically substantiated and practically developed.
Keywords: the personality - oriented approach; pedagogical competence; teaching methods